Autonomy Of The Algerian Central Bank In The Era Of Economic Reforms (A Normative Juridical Study Of Monetary And Credit Law) - Bakhouya Driss (European Scientific Journal, ESJ, 2016)
Globalization brings new challenges to the Algerian government. This issue implies a serious establishment of a domestic and a foreign economic stability in an attempt to confront the changes of the new economic wave. One of the reform requirements in this context is represented by the independent policy of the central banks. This consideration stems from the crucial role played by this institution in the economy (regulation of the money supply, organization of credits…). Algeria for instance embarked on this line of reform via various laws and jurisdictions. The study sheds light on the autonomy of the Algerian central bank through the law No. 03/11 in connection with the Monetary and Credit Law. The study states that the independence of the central and is a pivotal condition to increase the performance of the banking institutions in Algeria. The second point is that this autonomous policy of the central bank leads inevitably to a stabilization of the financial and economic indices of the country